2018
DOI: 10.1099/jgv.0.001128
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of amino acids in the H1-haemagglutinin to H3 residues is required for efficient influenza A virus replication and pathology in Tmprss2 knock-out mice

Abstract: The haemagglutinin (HA) of H1N1 and H3N2 influenza A virus (IAV) subtypes has to be activated by host proteases. Previous studies showed that H1N1 virus cannot replicate efficiently in Tmprss2−/− knock-out mice whereas H3N2 viruses are able to replicate to the same levels in Tmprss2−/− as in wild type (WT) mice. Here, we investigated the sequence requirements for the HA molecule that allow IAV to replicate efficiently in the absence of TMPRSS2. We showed that replacement of the H3 for the H1-loop sequence (ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…We and others demonstrated earlier that Tmprss2 −/− mice are also resistant to H1 IAV infection. In these studies, infectious virus was detected at day two after infection in lung homogenates [5,6,12]. Thus, some residual replication was observed for H1 virus, whereas in our present study, PR8_HA(H2) virus was not able to replicate to detectable titers in Tmprss2 −/− mice.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations
“…We and others demonstrated earlier that Tmprss2 −/− mice are also resistant to H1 IAV infection. In these studies, infectious virus was detected at day two after infection in lung homogenates [5,6,12]. Thus, some residual replication was observed for H1 virus, whereas in our present study, PR8_HA(H2) virus was not able to replicate to detectable titers in Tmprss2 −/− mice.…”
Section: Resultscontrasting
confidence: 63%
“…In this way, results were independent of other gene segments from the donor bird virus and comparable to other studies in which the HA segment was exchanged and tested on an isogenic PR8 background [8]. For the generation of the PR8_HA(H2) virus, the HA encoding segment 4 from the avian virus was cloned by sequence and ligation independent cloning as described earlier [12] into plasmid pHW-2000 (kindly provided by Robert Webster, St. Jude, Memphis, USA) using primers 5′-gacctcc-gaagttgggggggAGCAAAAGCAGGGG-3′ and 5′-ttttgggccgccgggttattAGTAGAAACAAGGGTGTTTT-3′. Re-assorted virus was then rescued from plasmids as described earlier [13] with 300 ng of each plasmid, 7.5 μl TransIT-2020 (Mirus) in 250 μl OptiMEM (Gibco) using the H2 encoding plasmid and plasmids containing all other seven segments of PR8 (kindly provided by Robert Webster, St. Jude, Memphis, USA).…”
Section: Main Textsupporting
confidence: 71%
See 2 more Smart Citations
“…Thus, it appears that the conformation and exposure of the HA cleavage site loop may differ more than generally assumed among IAV subtypes and that the cleavage site of H3 may be more accessible to various proteases. A recent study showed that replacement of amino acids 320 to 328 (H3 numbering) of the C terminus of HA1 of pandemic H1 (L-R-N-I-P-S-I-Q-S-R2) by the H3 sequence (M-R-N-V-P-E-K-Q-T-R2) did not support proteolytic activation of the mutated H1 in TMPRSS2 knockout mice (44). However, proteolytic activation of H1 in TMPRSS2-deficient mice was facilitated by replacement of amino acid E31 of H1 with D31 of H3 together with substitution of amino acids 320 to 328 of the HA1 C terminus.…”
Section: Discussionmentioning
confidence: 99%